Medieval Scotland : crown, lordship and community (Edinburgh University Press, 1993)
Medieval Scotland brings together thirteen essays specially written in honour of Professor Barrow. The contributors explore central themes in the development of the medieval Scottish kingdom, a subject which Professor Barrow has done so much to illuminate. They analyse the interplay between Celtic and feudal influences; the political definition of the kingdom; crown-magnate relations; and the relationship between the local and national communities. A complete bibliography of Professor Barrow's writings to the end of 1992 is also included.